Authentic Materials Used by English Teachers in Students’ Vocabulary Mastery at the Junior High Schools - Sukmojati, Edi; Nurhayati, Lusi; Al Viana, Silvia; Syafirah, Dian (Journal of Language and Literature Studies, 2025)
Authentic materials, whinch include resources such as images, photos, videos, and radio content like radio broadcasts are increasingly recognized for their effectivness in enhancing language learning, particularly vocabulary acquistion. This study aimed to explore the types of authentic materials used by English teachers in enhance students’ vocabulary and examine how these materials contribute to students’ vocabulary mastery. Employing a qualitative descriptive design, this research involved four English teachers at SMPI NW Mumbang as the respondents. Data were collected trought close-ended questionnaires and semi-structured interviews, which were transcribed and analysed using data reduction, data display, and conclusion drawing. The findings revealed three primary types of authentic materials used by teachers including magazine articles, using film and listening to songs. Meanwhile, these materials were found to contribute significantly to vocabulary development by fostering high level of enthusiasm, increased motivation, more relevant vocabulary and high engagement attention. The study concludes that integrating authentic materials into vocabulary instruction enhances student interest and supports more effective learning. These findings underscore the importance of incorporating real-world content into English language teaching practices to improve vocabulary acquisition.